Obstetrics - Salah Abduljabbar, Hassan (IntechOpen, 2017)
Obstetrics is the field that deals with the well-being of the pregnant women as well as the labor and delivery of a healthy baby. Obstetricians work closely as neonatologists who deal with the care of the newborn baby to reduce chances of morbidity and mortality. The objective of obstetrics is to deal with diagnosis and treatment of pregnancy, antenatal care, and prevention of complication, collaborating with midwives to monitor pregnant women in labor, facilitating delivery and performing assisted procedures if needed as episiotomy, forceps delivery, vacuum extraction, and Cesarean section if indicated.